2007
DOI: 10.3892/ijmm.20.1.91
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I enhances cortisol secretion from guinea-pig adrenal gland: in vivo and in vitro study

Abstract: Insulin-like growth factor (IGF)-I is a ubiquitously synthesized peptide that, along with IGF-II, acts via the IGF-R type I receptor. IGF-I and its receptor are expressed in the adrenal gland of humans and bovines, the secretion of which they seem to stimulate. As in humans and cows, the main glucocorticoid hormone secreted by guinea-pig adrenals is cortisol, and hence we have studied the adrenocortical effects of IGF-I in this species. In vivo experiments showed that prolonged IGF-I administration raised the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…31 Previous studies have shown that the IGF1 signaling pathway plays an important role in regulating the expression of P450c21 and P450c11. 32 In the present study, we found that PCE could inhibit the fetal adrenal IGF1 signaling pathway expression, accompanied by an impaired adrenal structural and functional development, similar to the above description. Furthermore, when the adrenal IGF1 pathway expression was increased in adult PCE male offspring, the adrenal cross-sectional area and cortex Ki67 expression were close to the control level (87.5% and 78.6% of the control respectively), meanwhile, adrenal steroidal synthetases P450c21 and P450c11 were increased and CORT production was close to the control level.…”
Section: Gc-igf1 Axis Programming By Pce Probably Participated In Adrenal Development Abnormality Before and After Birthsupporting
confidence: 88%
“…31 Previous studies have shown that the IGF1 signaling pathway plays an important role in regulating the expression of P450c21 and P450c11. 32 In the present study, we found that PCE could inhibit the fetal adrenal IGF1 signaling pathway expression, accompanied by an impaired adrenal structural and functional development, similar to the above description. Furthermore, when the adrenal IGF1 pathway expression was increased in adult PCE male offspring, the adrenal cross-sectional area and cortex Ki67 expression were close to the control level (87.5% and 78.6% of the control respectively), meanwhile, adrenal steroidal synthetases P450c21 and P450c11 were increased and CORT production was close to the control level.…”
Section: Gc-igf1 Axis Programming By Pce Probably Participated In Adrenal Development Abnormality Before and After Birthsupporting
confidence: 88%
“…Corticoid receptors (CRs), including the mineralocorticoid receptor (MR) and glucocorticoid receptor (GR), are ligand-dependent nuclear transcription factors 19 . The insulin-like growth factor 1 (IGF1) signaling pathway is the core of the endocrine regulatory system, modulates adrenal cell proliferation, differentiation and metabolism, which play important roles in morphology and functional development 20 , 21 . Our recent studies have found that PCE could cause adrenal function abnormity in offspring rats, which was related to low- expression of adrenal steroid synthetase (the first type of programming) 12 , 22 and GC-IGF1 axis programming (the second type of programming) induced by fetal overexposure to maternal GCs 23 .…”
Section: Introductionmentioning
confidence: 99%
“…IGF1 expression in the adrenal gland begins in the second trimester of pregnancy, occurring only later than in the liver, and IGF1 can regulate adrenal development and functional differentiation (Han et al , 1988). IGF1 and IGF1R are widely expressed in the adrenal cortex, upregulating steroid synthase through phosphorylation of the PI3K/Akt pathway to promote steroidogenesis (Raha et al , 2007;Sirianni et al , 2007). Our previous research found that prenatal dexamethasone exposure (PDE) could cause adrenal dysplasia in offspring mice, accompanied by decreased serum corticosterone levels in maternal and fetal mice (Xu et al , 2011).…”
Section: Introductionmentioning
confidence: 99%